Evaluation of the stability of whipped egg white - Dalma Radványi; Réka Juhász; Csaba Németh; Ágnes Suhajda; Csaba Balla; József Barta (Czech Journal of Food Sciences, 2012)
An investigation was made into the effects of various egg white products and sweeteners on the stability and organoleptic properties of egg white foams. 12 foam products were prepared from egg white and sweeteners. The egg white was produced in the following forms: raw liquid egg white, pasteurised liquid egg white, liquid egg white treated at 55°C for 24 h, and spray-dried egg white powder. Three different sweeteners were used: sucrose, fructose-glucose syrup, and fructo-oligosaccharide syrup. The storage stability, firmness, adhesiveness based on the texture profile analysis, and organoleptic properties of the foams were evaluated. The flow curves of raw materials were also determined by means of a rotational viscometer. The results indicated that sucrose among the sweeteners and egg white powder among the egg white products are the most suitable for producing egg white foam and enhancing its stability. However, liquid egg white heat treated at low temperature also proved to be an appropriate choice for making stable egg white foams for the confectionery industry.